Robert B. Parker's The bridge [large type] - Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Cole and Hitch novel., 2014)
Territorial Marshals Virgil Cole and Everett Hitch are back in Appaloosa, where things have been exceptionally quiet. Then an ominous storm rolls in, bringing along a band of night riders with a devious scheme who show up at the Rio Blanco camp, where a three-hundred-foot bridge is under construction. When Sheriff Sledge Driskill and his deputies respond, and then go missing, Virgil and Everett saddle up to sort things out.